The topical segregation of penguins of genus Pygoscelis and antarctic shags (Phalarocorax bransfieldensis) - Smagol, V.; Molchanoff, S. (Ukrainian Antarctic Journal, 2016)
The penguin fauna succession is studied from the western part of Graham Land. Due to climatic changes (warming up) the distribution of Gentoo penguins is observed and decreasing of area for Adelie penguins is indicated too. Gentoo penguins began to make nests on the territory of Adelie penguins, which show signs of stenobiontness.